Synthetic mesh as a potential low-cost alternative to dermal matrix in mammary reconstructions - Francisco Jose Fontenele Bezerra; Rosely Moraes Gonçalves de Moura (Revista Brasileira de Cirurgia Plástica)
Introduction: The use of acellular dermal matrices (ADM) in immediate breast reconstruction with silicone prosthesis (IBRP) led to a decrease in the number of surgical procedures (concerning the silicone expander) secondary to mastectomy, allowing the use of silicone implants >300cc. Its high cost made large-scale employment impossible (mainly in countries outside the US). Synthetic meshes proved to be a viable and widely used alternative (mainly in Europe). This study aimed to identify any difference in the surgical efficiency of IBRP after mastectomy using biological (ADM) or synthetic materials. Methods: A search was performed in the PubMed and VHL last five years databases (preferably), using the keywords: "mammoplasty" and "mastectomy" and "surgical screens" and "acellular dermal matrix" and "breast implants" and "postoperative complications". Results: The incidence of infection, hematoma, skin necrosis, seroma, extrusion or loss of implant and capsular contracture found in the research revealed to be complications inherent to the preoperative characteristics of patients: age >65 years, body mass index (BMI) >30kg/m2, large breasts (more than 600g), extensive skin resections and skin incisions in inverted T, smoking, diabetes, hypertension, time of long removal of the drain in the postoperative period, radiotherapy in the pre/postoperative period and that reported postoperative complications were not related to the use of ADM or synthetic mesh. Conclusion: The consensus of the data presented shows that the IBRP with synthetic meshes produced aesthetic results comparable to the ADMs, with lower costs and complication rates.